The impact of new media technologies on persuasive communication in the time of global crisis - Ghofrani, Talayeh (Inderscience Enterprises Ltd, 2024)
Coronavirus global pandemic and the growing need of governments and health organisations to direct respected societies to conduct new behaviour and health protocols have stressed the critical role of persuasive communications. This paper intends to show how new digital technologies and social platforms have provided the effective tools and techniques required for such purposes. The paper focuses on different aspects of technology changes in persuasive communications, elaborates the critical factors for a persuasive strategy to be more effective, and shows how these factors can be used. The study classifies the main factors in provision and likelihood of acceptance of persuasive content and the role that technology plays in each factor. It also provides a new method for governments and health organisations to actuate the public into appropriate responses to the outbreak.
Keywords: persuasive communication; persuasive technologies; persuasive contents; new media technologies; COVID-19